MAPPING OF QTLS DETERMINING THE EXPRESSION OF AGRONOMICALLY AND ECONOMICALLY VALUABLE FEATURES IN SPRING WHEAT (TRITICUM AESTIVUM L.) GROWN IN ENVIRONMENTALLY DIFFERENT RUSSIA REGIONS - Yu. V. Chesnokov; N. V. Pochepnya; L. V. Kozlenko; M. N. Sitnikov; O. P. Mitrofanova; V. V. Syukov; D. V. Kochetkov; U. Lovasser; A. Börner (Вавиловский журнал генетики и селекции)
For the first time a set of 110 recombinant inbred lines of a spring wheat mapping population was evaluated in different ecogeographical regions of Russia. Thirty-nine economically important traits that manifest themselves at different stages of growth have been examined in each ecogeographical locality under study for five years. A total of 186 quantitative trait loci (QTL) with LOD scores above 2,5 were identified. We have determined 97 QTLs with LOD scores exceeding 3,0. QTLs for traits studied, mapped on 21 chromosomes, manifested themselves under contrasting environmental conditions with varying degrees of reliability. It has been shown that manifestation of identified QTLs can depend or not depend on the environment, but the evaluated quantitative traits interact and correlate with each other. Relationships of identified homologous and homoeologous QTLs with known major genes or QTLs responsible for the manifestation of the studied traits in wheat or other Triticeae genera are discussed. The identified QTLs may be of interest for further experiments on the genetic control of the corresponding agriculturally valuable traits and for marker assisted selection in wheat breeding.